Too much may be a bad thing: the difference between challenge and hindrance job demands - Kim, Hyunsu; Shin, Kanghyun; Hwang, Jaesang (Current Psychology, 2024)
Job demands and employee motivations are studied through a challenging-disruptive needs framework. However, studies on challenging demands show mixed results due to the difference in the level of demand and effect of moderating variables. In this study, based on the Yerkes-Dodson law and conservation of resources theory, the non-linear relationship between challenging demand and work engagement, linear relationship between hindrance demand and work engagement, and moderating effect of stress were verified. A total of 3914 people were surveyed. The results showed that hindrance demand had a negative linear relationship with work engagement. Moreover, challenging demand had a positive effect on work engagement till a certain level, but had an inverted-U relationship with a negative influence thereafter. Stress mindset moderated these relationships and the negative effects of challenging and hindrance demands weakened for a stress-enhancing-mindset. Based on these results, theoretical and practical implications and future research directions were proposed.
Keywords: Employee motivation; Job demand; Job stress; Stress mindset; Work engagement